2017
DOI: 10.15740/has/ajbs/12.2/209-222
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, divergence, correlation and path analysis in Foeniculum vulgareMill. germplasm

Abstract: The importance of fennel is well realized on account of its high remunerative prices, domestic consumption, medicinal value and means to get earn foreign exchange. Despite the economic importance of fennel, disease resistant, locally acceptable and high yielding crop. The present investigation was therefore, carried out to estimate the magnitude and nature of genetic variability in terms of variation, heritability, genetic advance and genetic diversity for different traits like seed yield per plant and yield c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…These characteristics may be emphasized for the mungbean breeding programme. Significantly positive correlation in seed yield per plant with number of seeds per pod and number of pods per plant have earlier been reported by Bisht et al (2014) and Bhutia et al (2016); Choudhary et al (2016) for biological yield per plant. Significantly positive correlation in seed yield per plant with harvest index was earlier reported by Gadakh et al (2013); Katiyar et al (2015); Jadhav et al (2019) and Gaur et al (2021).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…These characteristics may be emphasized for the mungbean breeding programme. Significantly positive correlation in seed yield per plant with number of seeds per pod and number of pods per plant have earlier been reported by Bisht et al (2014) and Bhutia et al (2016); Choudhary et al (2016) for biological yield per plant. Significantly positive correlation in seed yield per plant with harvest index was earlier reported by Gadakh et al (2013); Katiyar et al (2015); Jadhav et al (2019) and Gaur et al (2021).…”
Section: Resultssupporting
confidence: 70%
“…Direct positive effect on seed yield through biological yield and harvest index was earlier reported by Gadakh et al (2013) and Choudhary et al (2016); for number of pods per plant, number of seeds per pod, pod length, plant height and 100seed weight was earlier reported by Bhutia et al (2016), Choudhary et al (2016) and Dhunde et al (2021) in mungbean.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, Singh and Mittal (2003) showed that there is a positive and important relationship between seed yield and plant height, umbels number, TWF in sweet fennel. Conversely, Patidar et al (2017) found that plant height was importantly and negatively related with only the number of umbellate per umbel (-0.29*). In this study, it was determined that there is a significant but negative correlation at P <0.05 level between plant height and branch number (r = -0.570*).…”
Section: Resultsmentioning
confidence: 92%